Psycho-Cultural Perspective on the Formation of Entrepreneurial Culture of Minangkabau Tribe in West Sumatra Indonesia - Hafiz Rahman; Sri Oktavia; Eri Besra (Udayana Journal of Law and Culture, 2019)
This paper aims to examine and to discuss how entrepreneurial culture is formed from perceived values, cultural dimension, kinship system and informal cultural based entrepreneurial learning of a society. As the context of the research, it uses the Minangkabau tribe, which enjoys supportive social supports and where the culture of entrepreneurship is naturally accepted by the most of the tribe members as a part of their way of life. This paper considers and argues that perceived value, cultural dimension, kinship system and ‘merantau’ – an informal cultural based entrepreneurial learning of the tribe have brought direct and/or indirect positive impact to the creation of an entrepreneurial culture within the tribe. As the basis, a qualitative approach and analysis in terms of descriptive-reflexive observatory method is used to analyse the topic, which is further narratively and descriptively presented. Results of paper have shown the possible model of how perceived value, cultural dimension, kinship system and informal cultural based entrepreneurial learning can perform an entrepreneurial culture of a society, in which it is considered as the significant contribution in the research related to the culture and entrepreneurship.